ANALYSIS OF THE POINT SPECTRUM OF THE STURM-LIOUVILLE OPERATOR WITH CERTAIN BEHAVIOR OF POTENTIAL AT INFINITY - Asatryan, H. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
In the space L^2(R) the Sturm-Liouville operator L with certain behavior of potential at infinity is considered. We prove that the eigenvalues of L are simple and are finite in number.